(untitled) (Research, Society and Development, 2020)
The objective of this research is to verify how some of the main representatives and institutions of sport and political fields acted during the discussion, elaboration and implementation of Zico Law, mainly within the Legislative Assembly. The study with a qualitative and exploratory approach used documentary research to analyze the shorthand notes reffering to the interventions of federal deputies, representative of clubs, state federations, Brazilian Confederation, as well as representatives of the Government during the public audiences that discussed Zico Law drafting. Through discourse analysis, a significant difference occurring during the course of the law, which were resolved by compromise and mainly by the imposition of politics interests in the sports field.